Ectopic pregnancy: an analysis of risk factors, diagnosis and management - Manohar, Navya; Ramanujam, Sai Latha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Ectopic pregnancy (EP), implantation outside the uterine cavity, is a leading cause of first-trimester maternal morbidity and mortality. Tubal pregnancies constitute over 90% of cases, with risk factors including pelvic inflammatory disease (PID), assisted reproductive technologies (ART), and delayed childbearing. Advances in transvaginal ultrasonography and β-hCG assays have improved early detection, but challenges in diagnosis and management persist. This study examines trends, risk factors, and management outcomes of EP at Chettinad medical college, Kelambakkam. Methods: A retrospective, non-interventional study of 50 EP cases (Jan 2023-June 2024) analyzed patient demographics, clinical presentations, and treatment outcomes. Descriptive and inferential statistics (Chi-square test, p<0.05) were used for analysis via SPSS. Results: The mean age was 29.02 years (23-35). Abdominal pain (13 cases) was the most frequent symptom, followed by the classic triad (12 cases). Prior EP (13 cases), PID, and ART were primary risk factors. Unruptured EPs (17 right, 12 left) were more common. Medical management (19 cases) was initially used, but 15 required surgery post-failure. No significant correlation was found between risk factors and symptoms (Chi-square=57.64, p=0.85). Conclusions: EP predominantly affects reproductive-age women, with abdominal pain as the primary symptom and prior EP as the main risk factor. Diagnostic advancements improve outcomes, but challenges remain in optimizing medical management and recurrence prevention. Future research should refine diagnostic markers and treatment strategies to reduce morbidity and mortality.